ASPEK PENOLAKAN DALAM NOVEL THE STARS SHINE DOWN KARYA SIDNEY SHELDON SUATU ANALISIS PRAGMATIK - BINABA, WAHYUNI NOVITASARI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2014)
ABSTRACT Language is the most important part of human life. In communication, people do not only utter sentence but also transfer it into behavior. Rejection is a form of communication. Rejection refusing something of the hearer and rejection belongs to perlocutionary act. Rejection can be divided into direct rejection and indirect rejection. The research question of this research is focused on the rejection which is implemented by the author through his novel The Stars Shine Down. In collecting data, the writer paid attention to the utterances among the characters in the novel. The collected data were analyzed descriptively in terms of how rejection as perlocutionary act are found in the conversation among characters. The result shows that there are some aspects of perlocutionary in direct and indirect rejection, those are to bring hearer to know, to get hearer to think, to get hearer to do, irritate and distract attention. Â  Key Words : Rejection, Perlocutionary act, Pragmatics.